Corporate social reporting practices of top Indian software firms - Vijaya Murthy; Indra Abeysekera (Australasian Accounting, Business and Finance Journal, 2008)
This study examines the corporate social reporting practices and the motivations behind such practices of the top 16 software firms in India. The 2003-2004 annual reports were analysed using content analysis to examine social reporting relating to human resource and social relations, combined with 14 case study interviews that examined managerial motives behind corporate social reporting (CSR) relating to the sample firms. When findings were analysed using legitimation strategies, the results indicate that firms use dual strategies in reporting their human resource and social relations to legitimise their activities to stakeholders